Assessing multiple novel tracers to improve the understanding of the contribution of agricultural farm waste to diffuse water pollution - Granger, S. J.; Bol, R.; Dixon, L.; Naden, P. S.; Old, G. H.; Marsh, J. K.; Bilotta, G.; Brazier, R.; White, S. M.; Haygarth, P. M. (Cranfield University, 2010)
A study was undertaken on drained and undrained 1 ha grassland lysimeters to assess the effectiveness of multiple novel tracing techniques in understanding how agricultural slurry waste moves from land to water. Artificial fluorescent particles designed to mimic the size and density of organic slurry particles were found to move off the grassland via inter-flow (surface + lateral through-flow) and drain-flow. Where both pathways were present the drains carried the greater number of particles. The results of the natural fluorescence and delta C-13 of water samples were inconclusive. Natural fluorescence was higher from slurry-amended lysimeters than from zero-slurry lysimeters, however, a fluorescence decay experiment suggested that no slurry signal should be present given the time between slurry application and the onset of drainage. The delta C-13 values of >0.7 mm and <0.7 mm material in drainage were varied and unrelated to discharge. The mean value of >0.7 mm delta C-13 in water from the drain-flow pathways was higher from the lysimeter which had received naturally enriched maize slurry compared to the lysimeter which received grass slurry indicating a contribution of slurry-derived material. Values of <0.7 mm delta C-13 from the same pathway, however, produced counter intuitive trends and may indicate that different fractions of the slurry have different delta C-13 values.
Keywords: natural-abundance measurements temperate grassland soil particle-size fractions dung-derived carbon organic-matter c-13 abundance clay soil phosphorus sediment drainage